Aktivitas Kitinase dan Peroksidase dari Ekstrak Kasar Protein Asal Kalus dan Berbagai Jaringan Tanaman Trichosanthes cucumerina var. anguina - Sukma, Dewi; Poerwanto, Roedhy; Sudarsono, ,; Khumaida, Nurul; Artika, I Made; Wiyono, Suryo (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2012)
Chitinase and peroxydase are important bioactive proteins or are specific enzymes that are related to plant resistance to pathogens. The aims of the research were to analyze the chitinase and peroxidase activities of crude protein extract from calli, stem, leaves and roots of T. cucumerinavar. anguina. In the first experiment, chitinase and peroxydase activities were analyzed from in vitro calli, leaves and roots obtained from 2-month-old of field grown plants. The media for calli induction were Murashige and Skoog medium with addition of 1 µM NAA + 1 µM BA, 2 µM NAA + 2 µM BA, 3 µM NAA + 3 µM BA, or 4 µM NAA + 4 µM BA. In the second experiment, the chitinase and peroxydase activities from crude protein extract of roots, stems and leaves were analyzed. The extracts were from 3-week-old seedling (less than a month), 1-month and 2-month-old plants. The first and the second experiment results showed that crude protein extracts of plant roots from the field grown plants had the highest chitinase and peroxidase activities. Stem of field grown plants had the similar level of chitinase activities with the plant roots. Chitinase activities of in vitro calli were not significantly different from those of plant roots so that it could be used as an alternative for plant roots in studying chitinase from T. cucumerinavar. anguina. Chitinase activities in crude protein extracts of roots appeared constant whereas peroxidase tend to increase with plant age. Keywords: calli, enzyme activities, leaves, roots, stem